The use of Augmented Reality in the context of museums: the Brazilian portfolio of theses and dissertations until 2017 - Menezes, Graciela Sardo (2019)
The objective of this study is to identify and analyze within the literature from Brazilian Postgraduate programs theses and dissertations that investigated the use of digital technologies, namely Augmented Reality (AR) in museum spaces. It is justified in view of the development of the theme based on consolidated studies in Brazilian postgraduate programs and the identification of theoretical basis for future research. For this purpose, a simple, preliminary and exploratory search was used in the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior and in the Instituto Brasileiro de Informação em Ciência e Tecnologia Thesis and Dissertation Databases. The results pointed to a dispersed and little systematized production and the opportunity to create research protocols on the subject based on the data collected.